TQM in public sector: Key success factors / Hasni Abdullah, Zaeidah Mohamed Isa and Sharifah Zannierah Syed Marzuki - Abdullah, Hasni; Mohamed Isa, Zaeidah; Syed Marzuki, Sharifah Zannierah (2007)
All organisation improvement programs have one thing in common; their success depends on the effectiveness of many collective efforts, rather than a single heroic effort. Total Quality Management (TQM) has long been implemented and the implementation has inspired the growth of public sector, balanced and sustained the success of public sector throughout the years. This paper will examine three key success factors of TQM, namely the leadership characteristics, employee characteristics and organisational factors which will contribute to the excellence of UiTM Pahang. The study reveals that among the three factors, the role of managers or top leaders are pivotal to maintain a higher quality organization